A systemic model for lossy mode resonances (LMRs) - Imas-González, José Javier; Villar-Fernández, Ignacio del; Wanguemert-Pérez, Juan Gonzalo; Matías-Maestro, Ignacio Raúl; Molina-Fernández, Íñigo (Elsevier, 2024)
Lossy mode resonances (LMRs) have been widely employed for the development of sensors in the last years. However, the theoretical frameworks for LMRs are scarce and difficult to systematize, hampering the development of this technology. In this work, we propose a new systemic model for assessing LMRs in arbitrary waveguide configurations, based solely on modal analysis of the unperturbed waveguide and the waveguide with a thin film optimized for LMR generation. The model is first developed for a generic waveguide, and leveraged to design, for the first time, LMRs in a silicon nitride photonic wire waveguide. It is furthermore demonstrated that the model only requires a few modes to reliably describe LMRs in D-shaped fibers, reducing the computational cost of simulating them. Therefore, the suggested model is valid for both high and low contrast waveguides, and it is considered it provides new insights about LMRs, which will help in the design of new LMR-based devices and its extension to novel platforms.
Keywords: Telecomunicaciones; Lossy mode resonance (LMR); Systemic model; Photonic wire; D-shaped fiber